Formação e demanda profissional em tratamento temático da informação no Brasil: uma análise comparativa de conteúdos programáticos universitários e de concursos públicos em biblioteconomia - Pando, Daniel Abraão [UNESP] (2005)
The changes that occurred after the arrival of the Globalization and the appearance of new information technologies are strongly felt in all fields of society. These changes that greatly altered the work market push Education to the delineation of new approaches that match the necessities required by the new times. Within this context, we had as a goal an analyses among the education contents that are dealt with in the Information Thematic Treatment offered by the librarianship, that is: Universidade Estadual Paulista - UNESP; Universidade de São Paulo - USP; Universidade Estadual de Londrina - UEL and Universidade Federal de São Carlos - UFSCAr comparing them to the content requirements in the ITT field delimited from the public exams which represent a share of the working market for the Brazilian librarian that allows a preliminary thematic comparison between the educational reality and the professional reality of the field studied. The adopted methodology was the quality approach with the utilization of content analysis so as data could be analyzed. To do so, the research had as its staring point the hypothesis that that was a distance between the contents taught by schools and those required by the public examinations. The hypothesis was partially confirmed because the teaching plans demonstrated, through analysis, that they are ahead of the public examinations requirements concerning the Information Thematic Treatment because while these examinations present a generic and traditional aspect to the schools as a whole, they go farther from what is required in the examinations, mainly in aspects concerning interdisciplinaridades and the intrumentalidades. One can observe that the aspects related to the documentation / thematic representation and techniques of description elaboration are dealt with in proposals at these examinations but they... (Complete abstract, click electronic address below)